Essence of religion, culture and indigenous language in a unified sexuality education system - Sibanda, Lidion (HTS teologiese studies, 2023)
Sexuality education is fundamental in higher and tertiary education institutions (HTEIs). Evidence suggests that its effective education is through translations into the first language of learners. However, in global and multilingual cultural communities such as HTEIs, the foundations for these translations are still a researchable area. Notably, in HTEIs adolescents, young adults and adults co-exist and therefore, any translations must be toned to balance across these groups. The aim of this study was to establish strategies that could enable sexuality educators to effectively transfer information that is steeped in indigenous language, religious and cultural meaning without precipitating stigma and taboo issues. The study setting was the National University of Science and Technology where a cross section of indigenous cultures, languages and religions co-existed with other global cultures. A University Community-based Participatory Research (CBPR) methodology was administered by the researchers using a Delphi research approach to students and staff. Multilingual, multilayered, multireligious, and multicultural nature of the setting presented serious challenges that compromised the prevention of stigma and taboo issues when dealing with sexuality education. We recommend that the strategy to present sexuality education in indigenous languages to the generality of HTEIs population should, in the first instance, involve systematic identification of appropriate interventions that are religious, cultural, and language-specific.Contribution: This research reveals paramount ethical and religious violations that have a potential to precipitate opportunistic sexual relationships that may lead to impediments in capacity building for learners. This research can be utilised by academics on the field of Practical Theology, specifically youth ministry and pastoral care.